A modified Elliptic Curve Cryptography Technique for Secur-ing Wireless Sensor Networks - Chanti, Yerrolla; Naik, Dr. K. Seena; Mothe, Rajesh; Yamsani, Nagendar; Balija, Swathi (International Journal of Engineering and Technology, 2018)
Despite rapid growth in the WSNs, it involved in all the fields of science and engineering. So due to wide usage, it is more prone to security threats.Â It is imperative to sketch an effective key management scheme for WSNs and take in consideration the confined characteristics of sensors. In this paper, a modified version of security is provided to wireless networks with the help of elliptic curve cryptography (ECC). With this benefits, this scheme works on the principle of converting given plaintext to appropriate ASCII values based on the doubling operations provided in encryption that can reduce the computation complexity to a lot.